Multi-band hybrid fractal shape antenna for X and K band applications - Nadal Shareef, Ammar; Abdulhussein Mohammed, Abbas; Basim Shaalan, Amer (International Journal of Engineering and Technology, 2018)
Fractal shapes has unusual properties. These unique features will affect antenna parameters when designed in fractal shapes. Two fractal shapes combined together to generate new fractal shape dipole antenna. Seirpinski and modified Koch fractal shapes allow this antenna to operate at too far apart frequencies lies in X and K band. Fractal dimension of modified Koch is found to be 1.08 which led the antenna to be electrically small. This is explaining the resonant points at higher frequencies. Uniting X and K band in single antenna will make the possibility of combining the applications of these two bands in one device. Good results have been obtained from calculating antenna parameters.